Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Impor Dengan Religiusitas Sebagai Variabel Moderating (Studi Kasus : Mahasiswa Program Studi Ekonomi Islam UIN Sumatera Utara) - Adila Husna; Nur Ahmadi Bi Rahmani; Muhammad Syahbudi (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
At this time, very many foreign products, especially food,enter Indonesia, according to the BPS, imports of consumer goods in 2021 have increased by 20,182.8 million US dollars. With the increase in the number of imported goods, it affects consumer behavior regarding consumption of goods so that consumer interest in imported products increases. However, the circulation of imported products are still many products that do not have a halal label on the packaging and certainly not guaranteed halal. This study aims to determine how the influence of halal literacy factors, halal labels, and product quality on purchasing decisions of imported products. This study uses a quantitative approach with questionnaire data collection techniques distributed to 75 respondents who are students majoring in Islamic economics UIN North Sumatra. This study used a moderated regression analysis method with the help of SPSS 22. The results of this study showed that the variable halal literacy significant effect on purchasing decisions worth 0.049 < 0.05. Variable halal label significant effect on purchasing decisions worth 0.036 < 0.05. Product quality variables have a significant effect on purchasing decisions worth 0.023 < 0.05. Religiosity was able to moderate the influence of halal literacy on purchasing decisions worth 0.037 < 0.05. Religiosity was able to moderate the influence of halal labels on purchasing decisions worth 0.023 < 0.05. And religiosity was able to moderate the influence of product quality on purchasing decisions worth 0.035 < 0.05.